Narra J Co-Editor-in-Chief is awarded as Highly Cited Researcher (HCR) 2021 - Harapan, Harapan; Wagner, Abram L. (Narra Sains Indonesia, 2021)
We acknowledge and congratulate Narra J Co-Editor-in-Chief, Dr. Kuldeep Dhama, as Highly Cited Researcher (HCR) 2021 by Clarivate. Dr. Kuldeep Dhama, is a Principal Scientist at ICAR-Indian Veterinary Research Institute in Izatnagar, India. He is a NAAS (National Academy of Agricultural Science, India) Associate, Fellow-Royal Society of Medicine (FRSM), UK, and has worked as Nodal Officer, WTO, and a member of Wildlife Health Specialist Group (IUCN). His research and teaching experience cover microbiology, immunology, virology, public health, medicine, and biomedicine. He is actively serving as Editor-in-Chief, Co-Editor-in-Chief, Editor, Associate Editor, Guest Editor and Member of Editorial Board for more than 15 scientific journals. Dr. Kuldeep Dhama role as Co-Editor-in-Chief of Narra J will enhance the quality of the Narra J one of the reputable journals in the near future. In his 27 years of research experience, he has published not only a great quantity of research (over 578 research publications indexed in Scopus with h-index of 50), but has published in highly respected journals such as Nature. Congratulations on an impactful career!